Enhancing Teaching and Learning: Libraries and Open Educational Resources in the Classroom. Issue 1 (2nd January 2016) - Davis, Erin; Cochran, Dory; Fagerheim, Britt; Thoms, Becky
Abstract : Academic libraries continually adjust services to adapt to the ever-changing landscape in higher education. In response to the broken textbook market, libraries are becoming actively involved in the open educational resources (OER) movement. Although there is not a formal program in place, librarians at Utah State University explored a collaborative approach to integrate OER in faculty members' courses. One goal of the effort was to work closely with faculty to consider course objectives and learning outcomes when evaluating and incorporating OER. This article identifies a streamlined process for targeting courses most suited for OER adoption and outlines a process of collaborating with teaching faculty to integrate relevant OER. The paper includes a detailed workflow that other libraries can easily adapt to make OER part of their faculty outreach toolkit.